The Arab tendency in the actions of the caliph Umar ibn al-Khattab and its impact on the loyalists (13-23 AH / 634-644 AD) (Journal of the College of Basic Education, 2023)
Studies on the personality of Caliph Umar ibn al-Khattab, may God be pleased with him, were characterized by a lot of veneration, which relied primarily on his strict personality, whether before or after Islam. And the actions approved by the Prophet, may God’s prayers and peace be upon him, with regard to his person, and most of them overlooked some important points in the narration of Ibn Al-Khattab’s biography, especially with regard to the variables that he brought about due to his diligence in the Islamic understanding of the facts and others, which greatly affected non-Arab Muslims in particular – the loyalist Those who fell under the influence of the procedures that the Caliph Omar Ibn Al-Khattab, may God be pleased with him, took, whether in the field of preferring Arabs over others or through other measures in the field of jurisprudence, the enactment of laws and the settlement of Arabs in cities and regions, and thus were one of the reasons that led to his death over others. Hand of a pro.Keywords: Umar ibn al-Khattab, Arab tendency, procedures, sebaa, marriage of competence, lineage, non-Arabs, loyalists.Note: Research extracted from the doctoral dissertation